Kajian Pokok dan Tokoh dalam Novel `Waiting for the Barbarians Karya John Maxwell Coetzee - Heri Dwi Santoso (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2013)
Subject matter with sociological approach in a literary study is very well-connected to the theme and social message. Meanwhile, when discussing about character with the same approach it usually talks about studies on race, class or gender. Social theories that can be used include feminism, Marxism, postcolonialism and some others. In connection to that, postcolonial theory is used in this study in order to analyse the subject matter and characters in „Waiting for the Barbarians‟, the object of this study. Waiting for the Barbarians is a novel written by John Maxwell Coetzee, a South American author.